How are older people's care preferences documented towards the end of life?. Issue 3 (June 2020) - Williams, Sue; Hwang, Kerry; Watt, James; Batchelor, Frances; Gerber, Katrin; Hayes, Barbara; Brijnath, Bianca
Abstract: Background: Meeting individuals' preferences is essential to achieve quality care at the end of life. Documenting these preferences in the healthcare system is an essential step to achieve them. Aim: To investigate the documentation of older people's care preferences including end of life care preferences in health records. Methods: Retrospective audit of health records for the last six months of life of people aged over 74 years who died in hospitals, residential aged care facilities, or community palliative care. Findings: Fifty records were audited, including 28 hospital, 12 residential aged care facilities, and 10 community palliative care records with overall 297 documented care preferences. 30% of preferences were recorded on institution-specific forms at admission which focussed on patients' medical/healthcare needs and less on personal/lifestyle preferences. Documentation mainly included clinical care preferences (35%), resuscitation plans (28%), and place of care (20%). Preferred place of death was not documented in 70% of cases. Increased documentation occurred closer to death with 63% of preferences recorded in the last week of life. Discussion: The low rates of recorded preferences, especially non-medical choices like preferred place of death, may indicate low rates of preference discussions and/or poor documentation of these conversations. The increase in documentation closer to death may be explained by increased care needs and higher rates of care place transitions towards the end of life. Conclusion: Discussion and documentation of older people's care preferences needs to be further encouraged within the healthcare system. It is essential not to wait for a crisis at the end of life to begin these processes.